Factibilidad para la creación de una empresa procesadora de cuero de ganado para el grupo artesanal del cantón Baba, provincia los Ríos, año 2015. - Andaluz Ati, Edison Fabián (2016)
The research was conducted in the canton of Baba Los Rios province. Its territorial extension is 516 km, is divided into three parishes Baba, Guare, Isla de Bejucal. It is located northeast of Canton Babahoyo, at a distance of 26 Km. and 40 Km. from the city of Vinces, with an extension area 165.66Km. In this territory 90 rural precincts and settle the cantonal head. 1.78333 latitude, longitude 79.6667 its boundaries are North Vinces Canton, Canton Babahoyo south and the Province of Guayas, this old town and Canton Babahoyo, Vinces Canton west and the Province of Guayas. Its terrain is flat with few elevations or hills without much height. semi-humid tropical climate, the average temperature is 24 to 26 ° C Hydrography The canton is an area of flooded land where the main rivers are the Arenal and Guare river. inductive, deductive methods and techniques such as direct observation and surveys was used to collect the necessary information and conduct market research, technical and financial study. To develop the market study surveyed 50 people who make up the Association of Artisans of Baba Canton. The results once made the technical diagnosis was identified risks, opportunities and competition to the creation of the company. In addition, he proposed a Theoretical Framework, it is the scientific theoretical foundation of this feasibility study which was determined through its information, the parameters necessary to move forward with the proposed project. . The financial study determined result in greater VAN get to zero means that the project is feasible because when invest $ 850,220.32 in five years you will have $ 124,551.51 more than the investment, the IRR is 15, 76% is affirmed the feasibility of the project because it is higher than the rate of cost performance and cost ratio is 1.15%. Keywords:  Feasibility  Market  leather Procesadora  craft Group